2013
DOI: 10.1016/j.geoforum.2012.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The morality of cheese: A paradox of defensive localism in a transnational cultural economy

Abstract: This paper uses the example of Slow Food International (SFI) and its promotion of artisanal cheese to examine how scale is produced around the defense of particular social relations of production. I argue that attempts by SFI to naturalize discursive configurations of rural/local/traditional express a particular politics tied to the anxiety of 'losing' imagined rural communities. However, SFI attempts to 'save' these communities are grounded not in planning or policy but in a kind of entrepreneurialism that lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 50 publications
(41 reference statements)
1
17
0
3
Order By: Relevance
“…Finally, agriculture and food production represent powerful cultural elements which link mountain environments with their human populations through long-established practices, such as traditional cheese-making and transhumance, often associated with cultural landscapes, built heritage, songs, festivals and routes of travel (Macdonald 2012;Soliva et al, 2008;Euromontana, 2004). Maintaining these cultural identities, practices and traditions engenders the building of trust and reciprocity in otherwise challenging environments (Soliva et al, 2008;Holloway et al, 2006).…”
mentioning
confidence: 99%
“…Finally, agriculture and food production represent powerful cultural elements which link mountain environments with their human populations through long-established practices, such as traditional cheese-making and transhumance, often associated with cultural landscapes, built heritage, songs, festivals and routes of travel (Macdonald 2012;Soliva et al, 2008;Euromontana, 2004). Maintaining these cultural identities, practices and traditions engenders the building of trust and reciprocity in otherwise challenging environments (Soliva et al, 2008;Holloway et al, 2006).…”
mentioning
confidence: 99%
“…Overton and Murray () have suggested that “fictive place” be studied as a factor of production and argue for the analysis of how fictions linking places to products are created and controlled. Using the example of cheese, MacDonald () explores the roles of cultural mediators such as Slow Food in “lifting a corner of the veil of fetishism” to selectively reveal aspects of the geographical and ecological origins of products while also “[reconfiguring] the veil through discursive projects that produce tradition, ‘the local’ and associated images of idyllic rurality” (p. 101).…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…A la vez, el disfrute de los productos autóctonos y la marca y valor añadido que se genera por ejemplo con los productos con Denominación de Origen, representan también un factor muy importante para el desarrollo económico regional (Bigné, 2011), situando en un territorio específico la calidad en la producción (Tresserras y Medina, 2008). En este contexto, la clave del éxito es integrar lo natural, lo local y lo tradicional (MacDonald, 2013), en una clara referencia a los deseos del consumidor que aprecia el consumo de un patrimonio gastronómico asociado a una identidad, a un paisaje.…”
Section: Generalidades Sobre El Turismo Gastronómicounclassified